Two new HLA‐B35 subtypes characterized in Spaniards: HLA‐B*35:270 and HLA‐B*35:273. Issue 5 (24th September 2015) - Sánchez‐Gordo, F.; Pacho, A.; Balas, A.; Arrieta, A.; Vicario, J. L.
<x xml:space="preserve">Abstract</x> Two new HLA‐B*35 alleles, B*35:270 and B*35:273, were characterized in the Spanish population.